3D trunk orientation measured using inertial measurement units during anatomical and dynamic sports motions - Brouwer, N. P.; Yeung, T.; Bobbert, M. F.; Besier, T. F. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Trunk motion is related to the performance and risk of injuries during dynamic sports motions. Optical motion capture is traditionally used to measure trunk motion during dynamic sports motions, but these systems are typically constrained to a laboratory environment. Inertial measurement units (IMUs) might provide a suitable alternative for measuring the trunk orientation during dynamic sports motions. The objective of the present study was to assess the accuracy of the three-dimensional trunk orientation measured using IMUs during dynamic sports motions and isolated anatomical trunk motions. The motions were recorded with two IMUs and an optical motion capture system (gold standard). Ten participants performed a total of 71 sports motions (19 golf swings, 15 one-handed ball throws, 19 tennis serves, and 18 baseball swings) and 125 anatomical trunk motions (42, 41, and 42 trials of lateral flexion, axial rotation, and flexion/extension, respectively). The root-mean-square differences between the IMU- and optical motion capture-based trunk angles were less than 5 degrees, and the similarity between the methods was on average across all trials "very good" to "excellent" (R = 0.85; R2 = 0.80). Across the dynamic sports motions, even higher measures of similarity were found (R = 0.90; R2 = 0.82). When aligned to the relevant segment, the current IMUs are a promising alternative to optical motion capture and previous presented IMU-based systems for the field-based measurement of the three-dimensional trunk orientation during dynamic sports motions and the anatomical trunk motions.